1975
DOI: 10.1177/107769907505200415
|View full text |Cite
|
Sign up to set email alerts
|

How Readers Perceive and Use a Small Daily Newspaper

Abstract: For consumers. "local with a random s a m d e of subscribers to-I information"-both news and advertising-overwhelms all other considerations. 'For example. wvenl unpublished studis conducted by L. Erwin Atwood at Southern Illinois Universfy Carbondak. 'Scvcnl such studies arc summarized by Bradlcy S Grcenbcrg and Michael E. Robff. "Mass Media Credihilitv. Research Results and C r i t k l laua." American Ncwrpapcr Publishers Association. Nrwr Rrwarrh Bulletin ,No. 6. Nor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Can we use it to help ourselves? 31 In suggesting such an approach to international reporting, however, we must consider the implications for journalistic values and style generally. For one of the attractions of negativism or conflict as a news value is surely that they are easy to apply.…”
Section: Discussioumentioning
confidence: 99%
See 1 more Smart Citation
“…Can we use it to help ourselves? 31 In suggesting such an approach to international reporting, however, we must consider the implications for journalistic values and style generally. For one of the attractions of negativism or conflict as a news value is surely that they are easy to apply.…”
Section: Discussioumentioning
confidence: 99%
“…30) Grotta, Larkin, and DePlois similarly found some evidence that the public prefers television as a source of foreign news. 31 One study which did try to bridge news flow and readership research, although without any particular attention to foreign news, was conducted in 1970 by L. Erwin Atwood.32 In comparing subscriber's and newsmen's story preferences, he expected to find concurrence on the priority of conflict as a news value, and limited concurrence on the prominence dimension. He found instead that relevance (impact) was the public's preferred news value, and conflict was second.…”
mentioning
confidence: 99%
“…It draws attention to the variability of media content and to the way that different media set different agenda. The limited research that has been done seems to suggest that there are no media-specific learning effects, nor is the recall/loss of spatial information media-specific (Helmreich 1976), and inter-media differences in content (especially differences between the press and television) may be less critical than is often imagined because there is evidence that the different media are not competitive so much as complementary sources of public information (Grotta et al 1975). It may even be that the agenda set by different media are very similar, as is borne out by American research showing that television and radio outlets owned by a newspaper do not differ in news coverage from independent television and radio outlets (Anderson 1971).…”
mentioning
confidence: 99%
“…Research also showed that newspaper advertising not only was considered more useful than any other newspaper but also enjoyed the highest readership of any kind of information content. 46 Abrams, Kaul, and Ma found a strong relationship between the perceived values of advertising and of news me~sages.4~ As the perceived value of advertising increased, so did the attitude toward the news, especially with middle-and lowerclass readers.…”
Section: Research In Uses and Guatifica-mentioning
confidence: 95%